The Scene and the Unseen: Mapping the (Affective) Rhythms of Wellington and Copenhagen (Revue D’études Interculturelles De L’image, 2017)
Abstract | The idea of rhythm has figured as a key conceptual and empirical motif in current research on urban space, place, and everyday life. This article offers a way of capturing, understanding, and interpreting the multifaceted rhythmical layout of urban spaces. It implements a rhythmanalytical methodology that draws on participant-generated photographs and mental maps as analytical tools in order to provoke compelling depictions of musical activity in the city. Based on current ethnographic fieldwork in the urban spaces of Wellington (Aotearoa/New Zealand) and Copenhagen (Denmark), this article proposes a fruitful technique of experience and experiment that seeks to recognise the interwovenness of socialities, atmospheres, object, texts, and images in people’s everyday lives and in this way affords opportunities for attending to the multiple rhythms underlying music-making in the city.Résumé | L’idée du rythme a été utilisée comme concept clé et motif empirique en recherche récente sur les espaces urbains et dans la vie quotidienne. Cet article apporte une méthode pour capturer, comprendre et interpréter les structures rythmiques complexes des espaces urbains. En introduisant une méthodologie rythmanalitique, cette méthode s’appuie sur des photographies et des cartes cognitives fournies par des participants comme outil analytique pour dépeindre l’activité musicale d’une ville. À partir d’une étude ethnographique sur les espaces urbains de Wellington (Aotearoa/Nouvelle Zélande) et de Copenhague (Danemark), cet article propose une technique expérimentale riche qui cherche à reconnaître les interconnections des milieux sociaux, des ambiances, des objets, des mots et des images dans la vie courante de chacun et offre ainsi une chance de suivre les rythmes multiples sous-jacent à la création musicale dans une ville.